Systematic identification and functional characterization of the CFEM proteins in fishscale bamboo rhombic-spot pathogen Neostagonosporella sichuanensis - Liang, Fang; Liu, Lijuan; Li, Chengsong; Liu, Yinggao; Han, Shan; Yang, Hua; Li, Shujiang; Hui, Wenkai; Liu, Long; Yang, Chunlin (Frontiers in Plant Science, 2024)
Fungal effectors play a crucial role in the interaction between pathogenic fungi and their hosts. These interactions directly influence the invasion and spread of pathogens, and the development of diseases.Common in fungal extracellular membrane (CFEM) effectors are closely associated with the pathogenicity, cell wall stability, and pathogenic processes of pathogenic fungi. In this study, we retrieved 19 CFEM proteins from the genome of Neostagonosporella sichuanensis. Systematic analysis identified five of these NsCFEM proteins that possessed signal peptides but not transmembrane structural domains as potential effectors. Of the five, NsCFEM1 and NsCFEM2 were successfully cloned and further investigated for their functions. Validation of subcellular localization and signal peptide secretion function indicated that NsCFEM1 was localized in the cell membrane and nucleus, whereas NsCFEM2 was exclusively observed in the cell membrane. Both were identified as secreted proteins. Additionally, NsCFEM1 inhibited Bax-induced programmed cell death in Nicotiana benthamiana, whereas NsCFEM2 did not induce or inhibit this response.NsCFEM1 was implicated as a virulence factor that contributes to fungal growth, development, stress response, and pathogenicity. NsCFEM2 was implicated in maintenance of cell wall stability. This study lays a foundation for elucidating the role of CFEM proteins in the pathogenicity of rhombic spots caused by N. sichuanensis.